Social determinants, health disparities and linkages to health and health care - Kronenfeld, Jennie J. (Bingley, U.K. : Emerald, 2013)
This volume looks at the key links between social determinants, health disparities and health and health care. There is a particular focus on macro-level systems and micro-level issues, including the examination of issues for patients, carers and providers of care. Coverage includes papers on geographical and place factors and disparities, SES and race/ethnicity factors, chronic care and serious health problems such as HIV/AIDs and kidney transplantation, comparative aspects and perceptions of health disparities. Starting with an introduction that reviews the crucial sociological literature on social determinants and health disparities, papers in this volume go on to cover key themes including ageing, barriers to care, ethnicity, social inequalities, the views of parents on their childrens care, and doctor/patient relationships.
Social determinants and health disparities / Jennie Jacobs Kronenfeld -- Addressing health disparities : understanding place in the role of social determinant interventions / Anne M. Hewitt -- The impact of neighborhood cohesion on older individuals' self-rated health status / Neale R. Chumbler, Tamara Leech -- Structural and hidden barriers to a local primary health care infrastructure : autonomy, decisions about primary health care, and the centrality and significance of power / Christopher R. Freed, Shantisha T. Hansberry, Martha I. Arrieta -- The effects of residential advantages upon rural residents' self-reported physical health and emotional well-being / James W. Grimm ... [et al.] -- Ethnic group differences in the utilization of preventive medical care services among foreign-born Asian and Latino adults in the United States / Bridget K. Gorman, Cindy Dinh -- Birth outcomes of patients enrolled in "Familias Sanas" research project / Kathryn Connors ... [et al.] -- Variations in parents' perceptions of their children's medical treatment : the effect of dissatisfaction on preventive care and unmet need / Hanna Jokinen-Gordon, Jill Quadagno -- An application of the Andersen model of health utilization to the understanding of the role of race-concordant doctor-patient relationships in reducing health disparities / Galen H. Smith, III, Teresa L. Scheid -- A generation skipped : an exploratory study of HIV/AIDS education and prevention services for older adults / Ann Marie Wood -- The sociology of chronic illness and self-care management / Mark Tausig -- Social capital, gatekeeping, and access to kidney transplantation / Nancy G. Kutner, Rebecca Zhang -- Contextualizing disparities : the case for comparative research on social inequalities in health / Sigrun Olafsdottir, Jason Beckfield, Elyas Bakhtiari -- Political ideology, party identification, and perceptions of health disparities : an exploratory study of cognitive and moral prejudice / Harry Perlstadt.
Print version record
Keywords: Social Science -- Disease & Health Issues; Social Science -- Ethnic Studies -- General; General practice; Personal & public health; Social medicine; Health -- Social aspects